Molecular clock calibration - Warnock, Rachel C. M. (Encyclopedia of Earth Sciences Series, 2015)
The incompleteness of the rock and fossil records means they cannot be used to establish a precise timeline for evolutionary history. The molecular clock provides a useful alternative, but the temporal calibrations required to estimate the substitution rate must be derived from paleontological evidence. The nonrandom nature of fossil preservation and recovery makes this extremely difficult. Although precise calibrations cannot be derived from the fossil record, they can instead be used to accurately define minimum and maximum constraints on divergence ages. The next challenge is to characterize the relationship between the constraints and divergence times. Approaches to do so have become increasingly complex and continue to progress to allow more information to be captured in the estimation of evolutionary times. Molecular estimates of times and rates will only ever be as accurate as the calibrations on which they are based, making it essential to embrace and understand the uncertainties inherent in the fossil record. Adopting a holistic approach through the integration of paleontological and biological expertise can make the molecular clock one of the most powerful tools in evolutionary biology.
CRIS-Team Scopus Importer:2020-10-13